Optimization of public-private partnership project management: challenges and solutions - Stepanov, M.; Legostayeva, A.; Fyliuk, H.; Jazykbayeva, B.; Yerzhanova, S. (Journal of Governance and Regulation, 2025)
The relevance of the study is related to the increasing importance of public-private partnership (PPP) for solving socially significant tasks and implementing large projects in conditions of a limited budget and lack of private investment. The aim of the work is to optimize the management of PPP projects by analyzing the current state, identifying key problems, and developing practical solutions. The research methodology includes the analysis of scientific literature and empirical observations. During the work, it was found that, despite Kazakhstan’s significant achievements in the development of PPP, such systemic problems as bureaucratic obstacles, financial risks, and insufficient readiness of facilities for transfer to private management remain. The main conclusions of the article emphasize the need to increase the competence of PPP participants, improve legislation, and apply new financial instruments (Stepanov et al., 2023). It is expected that the proposed measures will increase the volume of financing of PPP projects from 3,112 million tenge in 2023 to 4,697 million tenge in 2028. The paper highlights the importance of a systematic approach to PPP project management for the sustainable economic development of Kazakhstan (Stepanov & Legostayeva, 2022b).
Keywords: Project Management; Public-Private Partnership; Mechanism; Projects; State Management; Structural-Logistic Model; Challenges; Partnership